Answer:
Step-by-step explanation:
Substitution method can be applied in four steps. Step 1: Solve one of the equations for either x = or y = . Step 2: Substitute the solution from step 1 into the other equation. Step 3: Solve this new equation Happy too help!
Answer:
x = 5
Step-by-step explanation:
#7
20%•$300
$60
300-60
240
Hope this helps!!
Answer:
- 5(x - 4)(x + 4)
Step-by-step explanation:
Given
- 5x² + 80 ← factor out - 5 from each term
= - 5(x² - 16) ← x² - 16 is a difference of squares and factors in general as
a² - b² = (a - b)(a + b), thus
x² - 16 = x² - 4² = (x - 4)(x + 4)
Thus
- 5x² + 80 = - 5(x - 4)(x + 4) ← in factored form
Answer:
should be "d" though i haven't calculated it all exactly
Step-by-step explanation:
A : 85
B : 83
C : 82
D : 81